Defining Vocal Aesthetic Parameters in Tembang Sunda Cianjuran: A Case Study of the PTSC DAMAS Competition - Budiman, Arif; Jaenudin, Nanang (Mudra Jurnal Seni Budaya, 2025)
This study develops a conceptual framework to define a distinguished panembang (vocalist) in Tembang Sunda Cianjuran based on a case study of the PTSC DAMAS competition. Employing a qualitative research design, the study integrates triangulation methods data, techniques, and sources to enhance validity. Data were obtained through in-depth interviews with 12 key informants (including judges, panembang, and cultural experts), field observations, and document analysis. The analytical framework is based on A.A.M. Djelantik's aesthetic theory and uses Miles and Huberman's interactive model for data analysis. The study identifies five core parameters: Bener (accuracy), Merenah (proportionality), Genah (melodiousness), Alus (artistic refinement), and Mulus (flawless integration), each with context-specific indicators. These findings offer a culturally grounded yet methodologically rigorous model for evaluating performance quality in traditional Sundanese vocal arts. The proposed parameters offer a foundational step toward developing a more objective, transparent, and accountable judging system.